2006
DOI: 10.1007/s11239-006-8670-y
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms of drug-induced aspirin and clopidogrel resistance

Abstract: Aspirin (ASA) and clopidogrel have been identified as standard of care in the prevention of major cardiovascular events. Aspirin irreversibly inhibits the cyclooxygenase-1 (COX-1) enzyme, whereas non-steroidal anti-inflammatory drugs (NSAIDs) reversibly inhibit the COX-1 enzyme. An analysis of the literature revealed a statistically significant decrease in clinical benefit of ASA with concomitant administration of ibuprofen. Another NSAID, diclofenac, showed minimal effect on the inhibition of platelet aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…COX I catalyzes the transformation of membrane-bound arachidonic acid to thromboxane 1, a platelet agonist. Recently, it has been suggested that co-administration of NSAIDs with aspirin may interfere with the irreversible antiplatelet function of aspirin resulting thus in competitive interaction and attenuation of the antiplatelet effect [7] . However, a recent paper indicates that in vitro concurrent administration of aspirin and diclofenac potentiates the inhibition of platelet aggregation [8] .…”
Section: Discussionmentioning
confidence: 99%
“…COX I catalyzes the transformation of membrane-bound arachidonic acid to thromboxane 1, a platelet agonist. Recently, it has been suggested that co-administration of NSAIDs with aspirin may interfere with the irreversible antiplatelet function of aspirin resulting thus in competitive interaction and attenuation of the antiplatelet effect [7] . However, a recent paper indicates that in vitro concurrent administration of aspirin and diclofenac potentiates the inhibition of platelet aggregation [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Antiplatelet such as aspirin, clopidogrel, and ticagrelor are recommended to prevent thrombosis for patients with CHD with or without PCI. Clopidogrel is a pro-drug that requires metabolism primarily by CYP450 enzymes to become active metabolite [21,22]. The molecular target of the clopidogrel active metabolite is responsible for triggering platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, inappropriate activation of platelets is a key driver of common cardiovascular diseases, and platelets are a major therapeutic target in the prevention and treatment of conditions such as myocardial infarction. Limitations in the efficacy of platelet-targeted antithrombotics are due to drug resistance in a high proportion of individuals and incidences of bleeding associated with use of antithrombotics (Schroeder et al 2006). …”
Section: Platelets and Thrombosismentioning
confidence: 99%